Vitamin D Supplementation Modulates Platelet-Mediated Inflammation in Subjects With Type 2 Diabetes: A Randomized, Double-Blind, Placebo-Controlled Trial - Johny, Ebin; Jala, Aishwarya; Nath, Bishamber; Alam, Md Jahangir; Kuladhipati, Indra; Das, Rupam; Borkar, Roshan M.; Adela, Ramu (Frontiers in Immunology, 2022)
Background Recently, our group identified increased platelet-mediated inflammation in type 2 diabetes T2DM patients and it is a well established risk factor for diabetes complications particularly for the development of cardiovascular diseases CVD. Further, vitamin D is reported to play important role in the modulation of platelet hyperactivity and immune function. Although, vitamin D effect on platelet-mediated inflammation is not well studied. Hence, we aimed to investigate the effect of vitamin D supplementation on platelet-mediated inflammation in T2DM patients. Methods After screening a total of 201 subjects, our randomized, double blind, placebo controlled trial included 59 vitamin D deficient T2DM subjects and participants were randomly assigned to placebo 29 or vitamin D3 30 for six months. Serum vitamin D metabolites levels, immunome profiling, platelet activation, and platelet-immune cell aggregate formation were measured at baseline and end of the study. Similarly, serum levels of inflammatory cytokines/chemokines were assessed by multiplex assay. Results Six months of vitamin D supplementation increases serum vitamin D3 and total 25OHD levels from the baseline. Vitamin D supplementation does not improve glycemic control, and no significant difference was observed in immune cells. However, platelet activation and platelet immune cell aggregates were altered after the vitamin D intervention. Moreover, vitamin D reduces the serum levels of IL18, TNFα, IFNγ, CXCL10, CXCL12, CCL2, CCL5, CCL11 and PF4 levels as compared to baseline levels (p<0.05). Our Exvivo experiment confirms sufficient circulating levels of vitamin D reduces platelet activation and platelet intracellular reactive oxygen species. Conclusion Our study results provide evidence that vitamin D supportive therapy may help to reduce or prevent the disease progression and cardiovascular risk in T2DM patients by suppressing oxidative stress and platelet-mediated inflammation.